2015
DOI: 10.4172/2375-4494.1000236
|View full text |Cite
|
Sign up to set email alerts
|

Socio-behavioral Determinants of Overweight and Obesity in Egyptian Primary School Children

Abstract: Objectives: This study was conducted to assess socio-behavioral factors of overweight and obesity in primary Egyptian school children such as: residence, type of school, parent education, entertainment and dietary behaviors. Methods:The study was cross sectional and was conducted from May 2013 to August 2014 in Menoufia governorate in Egypt. 354 children aged 8-12 years brought consent from parents to participate and were enrolled in the study. The BMI percentile for students was calculated using a percentile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Furthermore, higher prevalence of obesity was positively associated in the age group of 6–9 years with male gender as well as regularity of father's employment which translate into a good socioeconomic status in our results ( Table 4 ). It confirms previous study results which reported a positive association with male gender as well as middle socioeconomic status and highlights that Fayoum Governorate follows the same trend regarding factors of obesity [ 35 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, higher prevalence of obesity was positively associated in the age group of 6–9 years with male gender as well as regularity of father's employment which translate into a good socioeconomic status in our results ( Table 4 ). It confirms previous study results which reported a positive association with male gender as well as middle socioeconomic status and highlights that Fayoum Governorate follows the same trend regarding factors of obesity [ 35 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…40 In Egypt the prevalence rate of overweight and obesity ranged between 31->40%. In one study 42 girls were more overweight and obese than boys while other studies 44,45 showed slight variations. In Libya, two studies showed a prevalence range of 9.5-28.2%.…”
Section: Overweight and Obesity Prevalence Among School Children In Amentioning
confidence: 85%
“…It ranged from 11.1 to 23.7% and 8.2 to 19.5%, respectively, in 5 studies conducted between 2010 and 2020. (26)(27)(28)(29)(30)(31) Only two percent or less of children are thin. (16) In 2016, the prevalence of obesity among school-aged children (6-9 years old) in the Eastern Mediterranean Region (EMR) was 10.5%, while the prevalence of overweight was 22.5%.…”
Section: Egypt's Nutrition Profile For Achieving Global Nutrition Tar...mentioning
confidence: 99%